IMPROVEMENT OF OVERDUE RECEIVABLES AND PAYABLES AND THEIR AUDIT (International conference on multidisciplinary science, 2025)
The efficient management of overdue receivables and payables is critical for maintaining financial stability and operational continuity within organizations. This article explores strategies for improving the management of overdue accounts and presents an enhanced framework for their audit. By integrating contemporary digital tools and aligning with regulatory requirements, the study offers practical solutions for addressing key challenges associated with overdue accounts. The findings are expected to provide actionable insights for financial managers, auditors, and policymakers.